Need to know : social science research methods - McIntyre, Lisa J. (Boston : McGraw-Hill, 2005)
This accessible, alternative approach to mainstream Research Methods titles is written for students who will need to interpret social research in their careers and, more than likely, have opportunities to do research. The book;s focus is on equipping students with the tools both to evaluate research done by others and to do their own research. Exercises in the text help students develop skills and strategies for research, including Internet assignments for finding and evaluating sources. The text provides students with a solid grounding in the relevant aspects of the philosophy of science and thoroughly explains the differences between quantitative and qualitative research methods.
-- Why you need to know : an introduction -- The nature of the scientific enterprise -- The logic of inquiry -- The vocabulary of science -- Doing the right thing : ethics in social research -- Sampling -- Elements of research design -- Experiments -- Survey research : Part 1 : the art of asking questions -- Survey research : Part 2 : design and implementation -- Unobstrusive methods -- Qualitative research methods.
Includes bibliographical reference (pages 287-290) and index.
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Methodology; Sociology -- Research -- Methodology; Sociology -- Methodology